THE INFLUENCE OF SCHOOL CLIMATE ON LEARNING EFFECTIVENESS MEDIATED BY STUDENT LEARNING MOTIVATION - Ratnaningsih, Nining; Supardi, Endang; Kurjono, Kurjono (Research and Development Journal of Education, 2025)
This study aims to analyze the effect of school climate on learning effectiveness mediated by student learning motivation at SMAN 1 Cipeundeuy, Subang Regency. This study uses a quantitative approach with a survey method involving 146 students selected through purposive sampling. Data collection was conducted using a unipolar positive numerical scale questionnaire of 1–5 and analyzed using path analysis with SmartPLS 3. The results showed that school climate had a positive and significant effect on learning effectiveness, school climate has a significant effect on learning motivation, and learning motivation has a significant effect on learning effectiveness. In addition, learning motivation significantly mediates the relationship between school climate and learning effectiveness. These results indicate that a positive school climate can increase students' intrinsic motivation, which in turn strengthens learning effectiveness. This study supports the Self-Determination theory, which emphasizes the importance of autonomy, competence, and relatedness in learning. These findings have practical implications that strengthening a positive and supportive school climate is an important strategy in improving the quality of learning and student achievement.